Development and characterization of graphite nanocomposite green electrochemical sensors for multiplex detection of antioxidants and DNA bases / Ng Khan Loon - Ng , Khan Loon (2017)
Graphite material is abundantly available from recyclable sources such as used alkaline dry batteries. It possesses unique polymorph with free valence sp2 hybridize carbon that can potentially interact with various nanomaterials. Sensors that based upon glassy carbon (GCE) or silica have been widely studied, but limited to multiplex analysis because of lacking in overpotential, effective surface area (Eff A) and electrocatalytic properties. In this Ph.D. study, the potential use of graphite obtained from used battery was explored as electrochemical sensor; where electrode surface modification with different nanomaterials was conducted to overcome these limitations. The practicability use of the developed sensors was tested for multiplex detection of anti-oxidants and DNA bases in real samples. Au−NPs/graphite sensor was successfully developed from graphite that obtained from used battery. In comparison to bare graphite, the deposited gold nanoparticles have improved the Eff A and heterogeneous electron transfer rate (ks) of the sensor by 3−folds. With larger electrode surface active sites (Eff A), more redox reaction could be accommodated by the sensor before the surfaces get saturated. The Au−NPs/graphite was successfully utilized for myricetin analysis using square wave voltammetry (SWV) technique; with sensitivity improvement by 2.5 folds, low limit of detection (LOD), and high accuracy that fit for beverages samples analyses. Besides, the developed graphite nanocomposite electrochemical sensor was also explored for the multiplex measurements of BHT, BHA, and TBHQ in various food samples using linear sweep voltammetry. Monitoring of these additives level in food is important especially since consumption of these substances above 3000 μg g−1 can promote cancer proliferation. The reliability of Au-NPs/graphite sensor was challenged by liquid chromatography (LC), where results correlation above 99.0% was achieved. Addition of sodium lauryl sulphate during sample extraction was found to amplify the sensor detection signal. Sensors with low LOQ, high accuracy, wide linearity, good precision, spike recovery and selectivity allow it for potential use in regulatory control. The performance of graphite was further explored using different combination of nanomaterials, and used for multiplex analysis of adenine, guanine, thymine and cytosine. Au−ErGO/MWCNT/graphite was developed using electro-codeposition of gold nanoparticles and graphene (ErGO). Electrochemical characteristic studies showed significant improvement in the ks, OP and electrocatalytic activity of the sensor. These have attributed to the remarkable applied potential range especially in cytosine detection that can be extended up to 1.4 V without being oxidized. Study of DNA composition has been an interesting research topic especially in DNA damage and genotoxicity study. The reliability of the sensor was confirmed with LC method, where a result correlation of 103.7% was achieved with the sensitivity, selectivity and accuracy that are comparable to LC. In conclusion, the objective of my Ph.D. study has been successfully achieved with the development of Au−NPs/graphite and Au−ErGO/MWCNT/graphite electrodes for multiplex detection of anti-oxidants and DNA bases, respectively. Future development on miniaturizing graphite sensor can be potential study for on-site analysis.